The role of electronic word-of-mouth in shaping brand image and driving purchase intention - To, Anh Tho; Nguyen, Kim Quoc Trung (Journal of Finance - Marketing Research, 2025)
As the influence of electronic word-of-mouth (eWOM) continues to grow in the digital marketplace, questions arise about its reliability and the extent to which it truly shapes consumer intention. This study seeks to investigate the critical role of eWOM in shaping brand image and driving purchase intention, with a particular focus on the dimensions of eWOM quality, quantity, and source credibility. The objective of this research is to provide a comprehensive understanding of how these eWOM factors influence brand image and purchase intention in an era dominated by online interactions. Utilizing data from 268 Vietnamese consumers, this study employs Structural Equation Modeling (SEM) and SmartPLS software to assess the relationships between the variables. The findings reveal that all three eWOM dimensions - quality, quantity, and source credibility - exert a significant positive influence on brand image, which in turn strongly affects purchase intention. Notably, eWOM quantity and source credibility were found to have a more substantial impact on brand image than eWOM quality. These results underscore the urgency for businesses to strategically manage online reviews and ensure the credibility of review sources to enhance brand perception and foster higher purchase intentions. The study provides insights for marketers and brand managers seeking to optimize their eWOM strategies in the competitive digital marketplace.